2008
DOI: 10.1590/s1678-91992008000100019
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and acute-phase serum proteins as markers of inflammatory regression during pulmonary tuberculosis treatment

Abstract: Tuberculosis is still increasing and was declared a worldwide sanitary emergency by the World Health Organization (WHO) in 1995. Its control is difficult due to long treatment duration and lack of markers of treatment success or failure. Cytokines such as IFN-γ and TNF-α, a central factor in immune response against Mycobacterium tuberculosis, are responsible for the interaction between T lymphocytes and the infected macrophage and are also produced during this interaction. As proinflammatory cytokines have a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
2
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 0 publications
2
23
2
11
Order By: Relevance
“…Differences could be caused by altered levels of plasma proteins (BDQ is Ͼ99.99% bound [11], and the concentration of plasma albumin is decreased in patients with TB [35] or TB/HIV coinfections [36]), altered bioavailability (37), or malnutrition. BDQ and M2 exposures were generally lower in patients with MDR-TB than would be expected based on data from healthy volunteers, and differences in bedaquiline CL and bioavailability have been shown (11,24).…”
Section: Discussionmentioning
confidence: 99%
“…Differences could be caused by altered levels of plasma proteins (BDQ is Ͼ99.99% bound [11], and the concentration of plasma albumin is decreased in patients with TB [35] or TB/HIV coinfections [36]), altered bioavailability (37), or malnutrition. BDQ and M2 exposures were generally lower in patients with MDR-TB than would be expected based on data from healthy volunteers, and differences in bedaquiline CL and bioavailability have been shown (11,24).…”
Section: Discussionmentioning
confidence: 99%
“…BDQ, though, is extensively bound to plasma proteins, Ͼ99.9% (16), and it is known that levels of certain proteins are altered in patients with active TB. In general, the albumin level is decreased, while the level of ␣1-acid glycoprotein (AAG) is increased (34). It has also been reported that albumin levels are even further decreased in TB patients coinfected with HIV (35).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the activation of the immune system mediates the systemic inflammation seen in the disease [4][5][6]. An increase in C-reactive protein (CRP), due to increased hepatic synthesis of acute phase proteins, and an increase in ESR follow the inflammatory process and hence these parameters are used in the diagnosis and follow-up of patients [7]. Studies have proved that CRP can serve as a sensitive indicator of activity of tuberculosis and the return to normal values of initially elevated CRP levels may indicate a good therapeutic response [8].…”
Section: Introductionmentioning
confidence: 99%